Valores y juventud: una perspectiva antropológica. - Grebe, María Ester (Revista Chilena de Humanidades, 2016)
The main point of this paper is to bring to our attcntion a number of contributions to Social Anthropologv relating to value sys tems or to value orientation in voung people. while considering factors such as in -culturization, identity, ancl syvmbology characteristic of this stage of life. Pro f. Grebe goes on to articulate a panorama of values in the sphere of cultural behaviour, showing their effect on the eclucational systems. She believes in the need to understand thc values of youth within their own symbolical context, in order to arrive at a productive dialogue with those involved in this period of life.